Expression of minor cartilage collagens and small leucine rich proteoglycans may be relatively reduced in osteoarthritic cartilage - Nobuho Tanaka; Toshiyuki Tashiro; Yozo Katsuragawa; Motoji Sawabe; Hiroshi Furukawa; Naoshi Fukui (BMC Musculoskeletal Disorders, 2019)
Abstract Background In osteoarthritis (OA), cartilage matrix is lost despite vigorous chondrocyte anabolism. In this study, we attempted to determine whether altered matrix synthesis is involved in this paradox in disease progression through gene expression analysis and ultrastructural analysis of collagen fibrils within the cartilage matrix. Methods Cartilage tissues were obtained from 29 end-stage OA knees and 11 control knees. First, cDNA microarray analysis was performed and the expression of 9 genes involved in collagen fibrillogenesis was compared between OA and control cartilages. Then their expression was investigated in further detail by a quantitative polymerase chain reaction (qPCR) analysis combined with laser capture microdissection. Finally, collagen fibril formation was compared between OA and control cartilage by transmission electron microscopy. Results The result of the microarray analysis suggested that the expression of type IX and type XI collagens and fibrillogenesis-related small leucine-rich proteoglycans (SLRPs) may be reduced in OA cartilage relative to the type II collagen expression. The qPCR analysis confirmed these results and further indicated that the relative reduction in the minor collagen and SLRP expression may be more obvious in degenerated areas of OA cartilage. An ultrastructural analysis suggested that thicker collagen fibrils may be formed by OA chondrocytes possibly through reduction in the minor collagen and SLRP expression. Conclusions This may be the first study to report the possibility of altered collagen fibrillogenesis in OA cartilage. Disturbance in collagen fibril formation may be a previously unidentified mechanism underlying the loss of cartilage matrix in OA.